The Doug Purvis Memorial Lecture - Monetary/Fiscal Policy Mix and Financial Stability: The Medium Term Is Still the Message - Stephen S. Poloz (Bank of Canada, 2016)
Financial stability risks have become topical in the wake of the global financial crisis and the subsequent extended period of very low interest rates. This paper investigates the significance of the mix of monetary and fiscal policies for financial stability through counterfactual simulations of three key historical episodes, using the Bank's main policy model, ToTEM (Terms-of-Trade Economic Model). The paper finds that there is an intimate relationship between the monetary/fiscal policy mix and the dynamics of both private sector and public sector debt accumulation. No attempt is made to develop criteria for policy mix optimization, since it is clear from the model simulations that the appropriate policy mix is highly state-dependent. This finding points to the need for a coherent framework for weighing the relative financial and macroeconomic consequences of accumulating public sector versus private sector debt. Furthermore, the analysis suggests that there are potential benefits to ex ante monetary/fiscal policy coordination, and that Canada's policy framework - where the monetary and fiscal authorities jointly agree on an inflation target while enshrining central bank operational independence - represents an elegant coordinating mechanism.
Keywords: E37; E5; E63; 330; Economic models; Financial stability; Fiscal policy; Monetary policy framework